2016
DOI: 10.1111/1750-3841.13261
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Decontamination of Dried Alaska Pollock Shreds Using Corona Discharge Plasma Jet: Effects on Physicochemical and Sensory Characteristics

Abstract: Nonthermal techniques for microbial decontamination are becoming more common for ensuring food safety. In this study, a corona discharge plasma jet (CDPJ) was used for inactivation of microbial contaminants of dried Alaska pollock shreds. Corona plasma jet was generated at a current strength of 1.5 A, and a span length of 25 mm was maintained between the electrode tip and the sample. Upon the CDPJ treatment (0 to 3 min) of dried shreds, microbial contaminants namely aerobic and marine bacteria, and Staphylococ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The majority of studies on TVB-N of fish are conducted during storage, and no reports are available on changes in TVB-N values of fish as affected by immersing in PFL for proper comparison. However, it was reported that the TVB-N values of dried Alaska pollock shreds and semi-dried raw Pacific saury decreased with increasing the treatment time of corona discharge plasma jet exposure, with levels ranging from 15.68 to 19.04 and from 17.99 to 24.74 mg%, respectively [51] , [52] . In contrast, Olatunde et al [53] found no significant differences in TVB-N values between untreated Asian sea bass and those packaged in polyethene bags and exposed to DBD plasma and reported values of 6.63–6.71 mg N/100 g for the treated samples.…”
Section: Resultsmentioning
confidence: 98%
“…The majority of studies on TVB-N of fish are conducted during storage, and no reports are available on changes in TVB-N values of fish as affected by immersing in PFL for proper comparison. However, it was reported that the TVB-N values of dried Alaska pollock shreds and semi-dried raw Pacific saury decreased with increasing the treatment time of corona discharge plasma jet exposure, with levels ranging from 15.68 to 19.04 and from 17.99 to 24.74 mg%, respectively [51] , [52] . In contrast, Olatunde et al [53] found no significant differences in TVB-N values between untreated Asian sea bass and those packaged in polyethene bags and exposed to DBD plasma and reported values of 6.63–6.71 mg N/100 g for the treated samples.…”
Section: Resultsmentioning
confidence: 98%
“…A significant increase in TBARs values has been reported by Albertos et al (2019) in Atlantic herring treated at 80 KV for 5 min. When dried Alaska pollock shreds, semi dried squid and Gwamegi (semi-dried raw Pacific saury) were treated by corona discharge plasma jet (CDPJ), a significant increase (P<0.05) in TBARs values were detected (Choi, Puligundla, & Mok, 2016Puligundla, Choi, & Mok, 2018). According to these authors, that increase during the CDPJ treatment may be attributed to the further oxidation of primary lipid oxidation products by reactive species generated by the jet plasma.…”
Section: Lipid Oxidationmentioning
confidence: 99%
“…As shown in Figure , the plasma generating equipment consisted of a high‐voltage power supply, electrode unit, air blower and sample stand. CDPJ was generated using 220 V AC single‐phase power source having an output voltage of 20 kV DC, at a current of 1.50 A, as discussed in our earlier publications . Under high‐voltage conditions, a streamer type corona discharge in air was generated between tungsten lid electrodes.…”
Section: Methodsmentioning
confidence: 99%